C.1 - "Kothari, Rajni" (Delhi, 1988)
This book brings together the more important of Rajni Kothari's essays on world order, peace and survival. These writings span the long period of his involvement in the World Order Models Project, his Editorship of the journal Alter natives and his work as Programme Director of the United Nations University's programme on Peace and Global Trans formation. The book also includes his Dyason Memorial Lectures which he delivered in Australia in 1974, his inaugural address to the International Institute of Strategic Studies in 1975, his paper for the United Nations Conference on the Effects of the Existing International Order on the Pursuit of Human Rights in the Developing Countries in 1980 and his contribution to the Committee of Experts convened by the Secretary-General of the United Nations for the Year of Peace in 1985. His latest and most recent in this series, 'Peace as Technological Fix', delivered at the Conference on Conflict Resolution held in New Zealand in N 987, is also included here. Many of these writings dresses are either unpublished or published in a variety of scattered publications that are not easily accessible. By bringing them together for the first time, this book presents a thematic over view of Kothari's distinctive perspective on international and world affairs.
Keywords: Peace